The Determinant of HIV Testing on Housewives in The Pesisir Jember Area - Ida Nurmawati; Ervina Rachmawati; Faiqatul Hikmah (Universitas Aisyah Pringsewu, 2021)
The development of HIV / AIDS cases in Jember Regency from year to year also tends to increase, but people who take HIV tests have decreased. Most cases of HIV / AIDS are in the